Research on roof damage mechanism and control technology of gob-side entry retaining under close distance gob. (August 2022) - Liu, Hongyang; Zhang, Boyang; Li, Xuelong; Liu, Chengwei; Wang, Chen; Wang, Feng; Chen, Deyou
Highlights: The rock layer between the two coal seams is affected by repeated mining and is prone to rotation instability. Based on the "block-dispersions" theory, the structure and failure process of the roof of the roadway under the gob is analyzed. The floor stress distribution law after mining in the upper coal seam is calculated according to the elastic theory. Abstract: With the increase in energy demand and in mining intensity, the phenomenon of multiple coal seam mining has appeared in major coal mining countries. While the downward mining method is generally adopted and under the damage of the upper coal seam, the structure and stress environment of the coal roof are very different from those of a single coal seam in remining. The rock layer between the two coal seams is affected by repeated mining and is prone to rotation instability, which makes it more difficult to reserve gob-side entries along the gob in the lower coal seams. This article mainly targets the case of the gob in the Panel #11426 of Xieqiao Mine, and studies the failure mechanism and control technology of the gob-side entry retaining in short-distance coal seam. First, the floor stress distribution law after mining in the upper coal seam is calculated according to the elastic theory, and verified by FLAC 3D numerical simulation; secondly, the floor failure depth after the upper coal seam is calculated according to the elastic–plastic theory. Based on the "block-dispersions" structure, the failure process of the roof of the roadway under close gob is analyzed. Further, it is proposed during the roadway excavation, to adopt support methods such as erecting U-steel retractable supports and back-wall filling; during the mining and before the gob-side entry retaining, the installation of roof bolts (cables), the reinforcement of the roof of the area to be filled and the in-wall filling techniques etc. to control the surrounding rock of gob-side entry. The engineering test was carried out along the track at the Panel #11426 of Xieqiao Mine. The onsite monitoring showed that: the maximum subsidence of the reserved gob-side entry roof along the gob was 180 mm, and the maximum approaching distance of the two banks was 328 mm, which met the engineering requirements. The research results can provide guidance for the design gob-side entry retaining along gobs under similar mining geological conditions.